2017
DOI: 10.1111/bdi.12468
|View full text |Cite
|
Sign up to set email alerts
|

Serum phosphatidylinositol as a biomarker for bipolar disorder liability

Abstract: Objectives Individuals with bipolar disorder (BPD) exhibit alterations in their phospholipid levels. It is unclear whether these alterations are a secondary consequence of illness state, or if phospholipids and illness risk overlap genetically. If the latter were true, then phospholipids might provide key insights into the pathophysiology of the illness. Therefore, we rank-ordered phospholipid classes by their genetic overlap with BPD risk in order to establish which class might be most informative in terms of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 78 publications
0
16
1
Order By: Relevance
“…They found that inhibition of Vps34, a kinase phosphorylating phosphatidylinositol (PI) to PI(3)P, causes endolysosomal dysfunction with secretion of exosomes containing APP C-terminal fragments. Knowles et al (2017) recently reported that serum levels of PI, the precursor of phosphoinositides like PI(3)P and PI(3,5)P 2 , is negatively associated with a proxy of genetic susceptibility to BIP.…”
Section: Discussionmentioning
confidence: 99%
“…They found that inhibition of Vps34, a kinase phosphorylating phosphatidylinositol (PI) to PI(3)P, causes endolysosomal dysfunction with secretion of exosomes containing APP C-terminal fragments. Knowles et al (2017) recently reported that serum levels of PI, the precursor of phosphoinositides like PI(3)P and PI(3,5)P 2 , is negatively associated with a proxy of genetic susceptibility to BIP.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies identified a panel of metabolic biomarkers that could discriminate patients with BD from healthy controls (13)(14)(15)(16)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). Lan et al (14) found several differential metabolites in post-mortem brain tissue, indicating that the balance of excitatory/inhibitory neurotransmission is the core of BD.…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that isocitric acid played a key role in the onset of BD. Other studies has also identified some potential biomarkers for BD diagnosis both in blood and urine (15,16,(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). However, the patients included in these studies were in different episodes.…”
Section: Introductionmentioning
confidence: 99%
“…Lan et al found several significantly altered metabolites in the brain tissue of BD patients [7]. Another study found that the serum phosphatidylinositol might be a potential biomarker for BD liability [8]. Our previous studies have also identified some potential biomarkers for BD diagnosis [9, 10].…”
Section: Introductionmentioning
confidence: 99%